(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The GST (Goods and Services Tax) is a courageous step toward reforming India's sprawling indirect tax system. The introduction of GST has resulted in a reduction of the tax burden and an increase in the country's ease of doing business. GST has two distinct effects: the first affects enterprises, while the second affects consumers, who bear the brunt of tax charges. In India, the unorganised sector and a portion of industry that benefit from the exemption will also significantly contribute to the country's GDP growth. The study's major purpose is to evaluate small business owners' awareness of the GST and to ascertain the actual impact. Recognizing that there will be an effect on productivity or sales, research is conducted to ascertain the magnitude of the impact and level of satisfaction. The report is based on a survey of 50 businessmen . A systematic questionnaire was used to collect data. The inquiry determined that while business owners are aware of the GST implementation and believe it is a fair tax system, the system lacks clarity and procedural simplification due to the requirement that they rely on CAs throughout the online submission process.